2011
DOI: 10.2220/biomedres.32.111
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in LEC rat liver: Suppression of carbonic anhydrase III by copper accumulation during hepatocarcinogenesis

Abstract: We examined age-related changes in the protein expression of carbonic anhydrase III (CAIII) in livers of Long-Evans with a cinnamon-like color (LEC) rats using an agouti color (LEA) rats as controls. The levels of the protein of CAIII in the liver of LEC male rats increased before 20 weeks of age, at the stage of acute hepatitis, and were decreased at 54 weeks of age, while those of CAIII in the liver of LEA male rats were highly expressed at all ages. In the normal LEA rats, CAIII showed sexual dimorphism. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Moreover, CA III may increase the Cells 2020, 9, 704 9 of 12 expression of the mesenchymal markers vimentin and several transcription factors of Slug and Twist through the FAK/Src signaling pathway to stimulate cell invasion and migration abilities similar to tumor metastasis. Relevant studies have suggested that lower CA III expression suppresses cancerous lesions in hepatoma-bearing rats in vivo and that the suppression of CA III accompanies hepatocarcinogenesis [39,40]. However, another study demonstrated that CA III could promote downstream hepatoma cell Sk-Hep1 transformation and invasion abilities through active FAK signaling pathways [29], which is similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, CA III may increase the Cells 2020, 9, 704 9 of 12 expression of the mesenchymal markers vimentin and several transcription factors of Slug and Twist through the FAK/Src signaling pathway to stimulate cell invasion and migration abilities similar to tumor metastasis. Relevant studies have suggested that lower CA III expression suppresses cancerous lesions in hepatoma-bearing rats in vivo and that the suppression of CA III accompanies hepatocarcinogenesis [39,40]. However, another study demonstrated that CA III could promote downstream hepatoma cell Sk-Hep1 transformation and invasion abilities through active FAK signaling pathways [29], which is similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…In line with our findings, Kuhara et al . reported no sexual dimorphism along with 20% percent higher expression of CA3 in males as compared to female LEC rats 55 . In contrast, elevated expression levels were reported in male Swiss albino rats after STZ induction 53 .…”
Section: Discussionmentioning
confidence: 90%
“…Carbonic anhydrase III (Ca3) is a cytosolic protein found in skeletal muscle, liver, and adipose tissue of mammals46. A significant decrease in Ca3 expression levels was found in rat hepatocarcinogenesis47. The downregulation of Ca3 levels by the treatment of ethanol and a hepatotoxicant of carbon tetrachloride was also reported124849.…”
Section: Resultsmentioning
confidence: 96%